The association between meeting physical activity guidelines and academic performance among junior high school adolescents in China-evidence from the China education tracking survey - Yang, Jie; Wang, Hai; Luo, Lin (Frontiers in Psychology, 2023)
Purpose: Purpose: The aim was to investigate the association between Chinese junior high school adolescents meeting the recommendations of the Physical Activity Guidelines for Chinese Residents (2021) and their academic performance. Method: Daily physical exercise time, screen time, and academic performance were collected from grade K8 adolescents (n=9449). Academic performance included standardized scores on Chinese, math, and English tests and responses to the School Life Experience Scale. Results:Compared to adolescents who did not meet the daily physical exercise and screen time recommendations, adolescents who met the daily physical exercise recommendation had increased school life experience self-scores, and adolescents who met the daily video screen time recommendation had increased standardized subject test scores and school life experience scores. Adolescents who achieved both daily physical exercise and screen time recommendations had higher math test scores compared to adolescents who achieved daily physical exercise recommendations. Adolescents who met both daily physical exercise and screen time recommendations had higher school life experience scores compared to adolescents who met daily screen time recommendations. Conclusion: Meeting the recommended physical activity guidelines for youth has a positive impact on improving both standardized subject test scores and school life experience scores for youth. Stakeholders should actively promote youth to follow the Physical Activity Guidelines for Chinese Residents (2021).